THE EFFECT OF DISTANCE LEARNING ON STUDENT EMOTIONAL AND SOCIAL WELL-BEING IN A PANDEMIC CONTEXT (Journal of Contemporary Philology, 2022)
Distance learning signifies a transformation in the sphere of education, characterized by use of technology as well as new ways of learning and cooperating. Despite the multitude of international scholarly conferences and panel discussions on how to improve the quality of online education, students were seldom consulted on how they personally coped with or felt about the introduced changes and whether they experienced emotional and social consequences from the shift to distance learning. This creates a strong need to investigate how distance learning affects student emotional and social well-being. Emotional well-being can be conceptualized as the balance of experienced feelings (positive and negative) and the perceived feelings (happiness and satisfaction) and is strongly connected to psychological well-being (personal growth, environmental mastery, autonomy) and social well-being (social integration and contribution) (Keyes 2007). The purpose of this study is to explore whether distance learning has an impact on student emotional and social well-being. Online survey research was conducted among 60 translation and interpreting students in North Macedonia, which results suggest that students are highly impacted from an emotional and social point of view. A variety of emotional intelligence-related activities can be integrated to improve specific areas from both academic and personal point of view, such as self-awareness, self-management, motivation and empathy as generic competences of key importance during isolated distance learning as well as for a future profession as translators and interpreters.
Keywords: emotional and social well-being; emotional intelligence; distance learning; emotions